Study of Storage Time on The Organoleptic Characteristics of Pineapple Drink Powder: Kajian Waktu Penyimpanan pada Karateristik Organoleptik Serbuk Minuman Nanas - Dian P. Prabowo., Ivy; Nareswara, Sebastian Farell (Universitas Muhammadiyah Sidoarjo, 2024)
Pineapple (Ananas comosus) is one of the tropical fruits with relatively affordable and stable prices because pineapple is not a seasonal fruit and the amount of its harvest in Indonesia is quite high. Pineapple is a fruit that is easily rotten, therefore efforts are needed to extend the shelf life of pineapple. One of them is by making pineapple drink powder. This study was analyzed by a hedonic test using 30 untrained panelists who were asked to provide an assessment of the aroma, color, and taste of pineapple drink powder and pineapple powder solution stored for 1,2,3, and 4 weeks. The results of this study can show that the longer the storage time of pineapple drink powder can reduce the panelists' acceptance of aroma, color, and taste. The results of this study showed that the assessment of aroma, color, and taste decreased from liking to disliking in the 4th week for both pineapple drink powder and the dissolved pineapple.